Saga of civil services - Narain, Yogendra (New Delhi, 2008)
The author traces the history of the Civil Services from the advent of British in India and highlights the changes that have taken place in the essential nature of the service. He emphasizes that it is no longer the 'Civil Services versus the Politician' syndrome that should govern administration.
Keywords: Civil service